2015
DOI: 10.1186/s12937-015-0121-1
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a food frequency questionnaire to estimate dietary intake among Lebanese children

Abstract: BackgroundNutritional status during childhood is critical given its effect on growth and development as well as its association with disease risk later in life. The Middle East and North Africa (MENA) region is experiencing alarming rates of childhood malnutrition, both over- and under-nutrition. Hence, there is a need for valid tools to assess dietary intake for children in this region. To date, there are no validated dietary assessment tools for children in any country of the MENA region. The main objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
86
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(110 citation statements)
references
References 66 publications
(87 reference statements)
14
86
3
5
Order By: Relevance
“…Few studies have published data of reproducibility of FFQ in children [1315, 3841] and only one, carried out in forty-seven Japanese children aged 6 years, used a period of six months to examine reproducibility, closer to the period used in our study [41]. The average of reproducibility coefficients in our study was 0.42, lower than that observed in the Japanese study that reported correlations higher than 0.50 for all nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have published data of reproducibility of FFQ in children [1315, 3841] and only one, carried out in forty-seven Japanese children aged 6 years, used a period of six months to examine reproducibility, closer to the period used in our study [41]. The average of reproducibility coefficients in our study was 0.42, lower than that observed in the Japanese study that reported correlations higher than 0.50 for all nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…More recently published studies have shown that FFQ may produce valid and satisfactory estimates of a wide range of food and nutrient intakes in preschool children of Greece [12], Lebanon [13] and Denmark [14]. However, there is clearly a need for more valid FFQs in preschool children in many countries including Spain, where, as far as we know, no valid FFQ exists for dietary assessment of food and nutrients in children aged 4 to 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Participants unable to recall the foods and quantities were not included in this analysis. Although this disadvantage, this approach is used as gold standard to validate other food intake methods like food frequency questionnaire [10], which was not applicable to our study since Indians food habits were different from the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Un número creciente de estudios en el mundo utilizan y validan cuestionarios de autorreporte para la medición de HA y de AF (Bauman et al, 2010;Bel-Serrat et al, 2012;Moghames et al, 2016;Pérez et al, 2011;Saeedi, Skeaff, Wong y Skidmore, 2016;Telford, Salmon, Jolley y Crawford, 2004;Wilson, Magarey y Mastersson, 2008). En Latinoamérica se encuentran cuestionarios validados en Brasil (Hinnig, Mariath, Mascarenhas, Dianezi y Pimentel, 2014), Chile (Lera, Fretes, González, Salinas y Vio, 2015) y México (Guerrero et al, 2014).…”
Section: Revistaunclassified